Incidence of germline BRCA1/2 mutations in women with tubo-ovarian high-grade serous carcinomas with and without serous tubal intra-epithelial carcinomas. Issue 1 (7th November 2019) - Dowson, Cassandra B; Stewart, Colin; O'Sullivan, Sarah; Pachter, Nicholas; Schofield, Lyn; Cohen, Paul A
Abstract : Objective: To compare the germline BRCA1 and BRCA2 mutation ( gBRCA ) status in women with high-grade serous tubo-ovarian and primary peritoneal carcinoma with and without serous tubal intra-epithelial carcinomas (serous tubal intra-epithelial carcinoma-positive vs serous tubal intra-epithelial carcinoma-negative). Materials and methods: A retrospective study was performed of patients in Western Australia diagnosed with high-grade serous tubo-ovarian and primary peritoneal carcinoma and referred for genetic counseling and gBRCA testing from July 1, 2014 to June 30, 2017. Histopathology reports were reviewed to ascertain whether serous tubal intra-epithelial carcinoma was present. Personal or family gBRCA status, family history, age at diagnosis, mode of treatment (neoadjuvant chemotherapy vs primary surgery), and stage were also recorded. Results: A total of 269 women with high-grade serous tubo-ovarian and primary peritoneal carcinoma were referred for genetic counseling and testing. 114 patients were excluded because the serous tubal intra-epithelial carcinoma status was not assessable or because patients did not attend for genetic assessment. 155 patients (55 serous tubal intra-epithelial carcinoma-positive and 100 serous tubal intra-epithelial carcinoma-negative) underwent genetic testing. gBRCA mutations were found in 27.8% of serous tubal intra-epithelial carcinoma-positive patients compared with 14.0% of serous tubal intra-epithelial carcinoma-negative patients (p=0.094). Of those found to have a gBRCA mutation, 89.7% reported a positive personal or family history of BRCA -related cancers. Conclusions: The gBRCA mutation detection rate in serous tubal intra-epithelial carcinoma-positive patients was nearly double that of serous tubal intra-epithelial carcinoma-negative patients. Factors such as a positive family history of BRCA -related cancers were seen at a higher proportion in the mutation positive women.